Pengaruh Kepemimpinan Etis dan Budaya Organisasi Terhadap Kinerja Karyawan Pada PT. Asuransi Umum Bumiputera Muda 1967 - Maudul, Angel; Pio, Riane J.; Runtuwene, Roy F. (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
This study aims to determine the influence of ethical leadership on employee performance, to determine the influence of organizational culture on employee performance and to determine the influence of ethical leadership and organizational culture on employee performance at PT. Asuransi Umum Bumiputera Muda 1967. A leader with high ethical leadership and organizational culture can influence individuals or groups to behave in accordance with organizational or corporate goals. Therefore, companies or organizations need to pay attention to matters that include leadership ethics and organizational culture so that employee performance can be developed for the progress of the organization or company. This research uses quantitative research method, with multiple regression analysis approach to know the level of influence between variables, and t test seen from the level of significance between variables, namely ethical leadership (X1), organizational culture (X2) and employee performance (Y). While to know the value of influence of ethical leadership variable and organizational culture together to employee performance seen from F count bigger dat F table. The results of this study indicate that ethical leadership and organizational culture have a positive and significant influence on employee performance, so the hypothesis that there is influence of ethical leadership on employee performance, there is influence of organizational culture on employee performance and there is influence ethical leadership and organizational culture on employee performance otherwise acceptable.